Significant role of molybdenum promoted TiO2 catalysts for carbon nanotubes production and their polymer nanocomposites. (2022) - Mitra, Rahul; Mandal, Saikat; Trivedi, Vivek; Valand, Jignesh
Abstract: Role of specific catalysts system is still a thrust area for the synthesis of carbon nanotubes. Titania-supported Fe and Co catalysts were prepared using the sol-gel and wet-impregnation method. These catalysts were used for the deposition of multiwalled carbon nanotubes (MWNTs) from xylene by the catalytic chemical vapour deposition (CCVD) technique at 800 °C. In the present work, the effect of the addition of molybdenum with monometallic catalyst had been investigated from the viewpoint of the growth of the carbon nanotubes (CNTs). The results showed that the presence of molybdenum in minor amount with Fe/Co-based catalysts can increase the amount of deposition of CNTs. CNTs-Epoxy resin composites were fabricated using prepared carbon nanotubes with a CNTs loading of 0.2 wt% and performed flexural testing measurement. These multi-components systems of titania and carbon nanotubes have a capacity to enhance many properties significantly for specific applications.